Ambipolar charge transport in films of methanofullerene and poly(phenylenevinylene)/methanofullerene blends - Choulis, Stelios A.; Tuladhar, Sachetan M.; Poplavskyy, Dmitry (My University, 2005)
Herein, we report experimental studies of electron and hole transport in thin films of [6,6]-phenyl C61 butyric acid methyl ester (PCBM) and in blends of poly[2-methoxy-5-(3′,7′-dimethyloctyloxy)-1,4-phenylenevinylene] (MDMO-PPV) with PCBM. The low-field hole mobility in pristine MDMO-PPV is of the order of 10–7 cm2 V–1 s–1, in agreement with previous studies, whereas the electron mobility in pristine PCBM was found by current-density–voltage (J–V) measurements to be of the order of 10–2 cm2 V–1 s–1, which is about one order of magnitude greater than previously reported. Adding PCBM to the blend increases both electron and hole mobilities, compared to the pristine polymer, and results in less dispersive hole transport. The hole mobility in a blend containing 67 wt.-% PCBM is at least two orders of magnitude greater than in the pristine polymer. This result is independent of measurement technique and film thickness, indicating a true bulk property of the material. We therefore propose that PCBM may assist hole transport in the blend, either by participating in hole transport or by changing the polymer-chain packing to enhance hole mobility. Time-of-flight mobility measurements of PCBM dispersed in a polystyrene matrix yield electron and hole mobilities of similar magnitude and relatively non-dispersive transport. To the best of our knowledge, this is the first report of hole transport in a methanofullerene. We discuss the conditions under which hole transport in the fullerene phase of a polymer/fullerene blend may be expected. The relevance to photovoltaic device function is also discussed
Keywords: Charge transfer; Electric currents; Esters; Fullerenes; Thin films; Methane